The Linnaeus household. Data from taxation lists, Uppsala University account books and Vita-texts. - Windahl Pontén, Annika (Uppsala University, 2020)
Data gathered during the PhD-project Identity and materiality in the household of Carl Linnaeus. The data consists of salaries and other payments registered in Uppsala University account books, information regarding which persons were members of the household according to taxation lists and lists of names from the autobiographical texts by Carl Linnaeus senior. There are information concerning the Linnaeus household, the Rosén von Rosenstein household and Carl Linnaeus junior.

the ZIP-file contains 4 excel-files and the documentation in a pdf-file.

Data insamlat och använt i samband med avhandlingsprojektet Identitet och materialitet i hushållet von Linné. Data består av uppgifter ur Uppsala universitets räkenskaper gällande löner och andra utbetalningar, uppgifter ur mantalslängder gällande vilka som mantalsskrivits i hushållet samt sammanställning av vilka namn som förekommer i Carl von Linné d ä:s självbiografiska texter, de s k Vitorna. Uppgifter finns gällande hushållet von Linné, hushållet Rosén von Rosenstein samt Carl von Linné d y.

ZIP-filen innehåller 4 excel-filer samt en dokumentationsfil i pdf.
Hushållet von Linné. Data ur mantalslängder, Uppsala universitets räkenskaper och Vita-texter.
Keywords: households; hushåll; servants; tjänstefolk; History, 18th Century; 1700-talshistoria; Humanities and the Arts; Humaniora och konst